ANALISIS DAMPAK INTENSITAS PENCAHAYAAN RUANGAN FARMASI DENGAN KELUHAN KELELAHAN MATA PADA PEKERJA DI RUMAH SAKIT MESRA KABUPATEN KAMPAR TAHUN 2020: ANALISIS DAMPAK INTENSITAS PENCAHAYAAN RUANGAN FARMASI DENGAN KELUHAN KELELAHAN MATA PADA PEKERJA DI RUMAH SAKIT MESRA KABUPATEN KAMPAR TAHUN 2020 - Erix Extrada; Muhamadiah Muhamadiah; Makomulamin Makomulamin; Ahmad Satria Efendi; Firman Edigan (STIKes Al-Insyirah Pekanbaru, 2020)
ABSTRACT Lighting is the amount of irradiation that is in a work environment needed to carry out a job properly. Based on observations, the lighting intensity of the pharmacy room at Mesra Hospital in Kampar Regency was not bright enough. The purpose of this study was to determine the lighting intensity of the pharmacy room and the impact on workers at Mesra Hospital, Kampar Regency. This type of research is descriptive qualitative. Interviews and observations were conducted with 5 informants. The location of the study was conducted at Mesra Hospital, Kampar District in May-July 2020. The results showed that the local lighting in the pharmacy room of the Mesra Hospital, Kampar Regency, measurements of the lighting intensity in the pharmacy room were carried out at the work table. The results of measuring the intensity of lighting in the pharmacy room using local lighting methods obtained a value of 74.1 lux. Based on the results of the study, it can be seen that the lighting in the pharmacy room of Mesra Hospital in Kampar Regency has not met the standards of the Regulation of the Minister of Health of the Republic of Indonesia Number 7 of 2019 concerning Hospital Environmental Health. Less bright lighting results in complaints of eye fatigue in workers. The complaints of eye fatigue experienced by workers are in the form of pain around the eyes, dizziness, drowsiness and pain around the eyes. Bibliography : 27 (2004-2019) Keywords : Intensity, Lux, Local Lighting, Eye Fatigue